Influence of Corporate Image, Digital Literacy, and Employee Experience on Employee Loyalty at PT. NSS Palopo - Tia Juliawati; Haedar Haedar; Edi Maszudi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of corporate image, digital literacy, and employee experience on employee loyalty at PT. NSS Palopo in 2025. Methodology: A quantitative approach was used with PLS-SEM analysis through SmartPLS 4. A total of 55 employees were selected using saturated sampling, and data were collected through a five-point Likert scale questionnaire. Results: Corporate image significantly affects employee loyalty, digital literacy, and employee experience. Employee experience also significantly affects digital literacy and employee loyalty, while digital literacy has no significant effect on employee loyalty. Findings: Employee loyalty is more influenced by employee experience and corporate image than digital literacy, with strong predictive power (R² = 71.1%). Novelty & Originality: This study offers novelty by examining the interplay of corporate image, digital literacy, and employee experience in a regional corporate setting in Palopo, a context rarely explored in prior research. Conclusions: Improving employee experience and corporate image is more effective than focusing only on digital literacy. Type of Paper: This paper is a research article.